Correlations of Perceived Flow, Perceived System Quality, Perceived Information Quality, and Perceived User Trust on Mobile Social Networking Service (SNS) Users’ Loyalty - Suki, Norazah Mohd (Journal of information technology research, 2012)
This research aims to examine the correlations of perceived flow, perceived system quality, perceived information quality and perceived user trust on mobile social networking service (SNS) users’ loyalty. Investigation of correlation between perceived user trust with perceived flow and user loyalty were also performed. Two hundred students were the subjects of a Malaysian university to answer survey questions on their currently chosen mobile social network system. The correlations between perceptual variables on mobile SNS were then analyzed and various causal relations deduced. Research findings indicate both perceived information quality and perceived system quality correlates with perceived flow and perceived users’ trust, which further correlate mobile SNS users’ loyalty. Perceived user trust correlates with perceived flow, and both factors correlates with user loyalty. Perceived flow is regarded as the strongest factor that correlates with users’ loyalty. The paper rounds off with conclusions and an agenda for future research in this area.